Identification and detection of genetic markers associated with antimicrobial susceptibility and evaluation of efflux pump mechanisms in Mycoplasma iowae - Dominika Buni; Áron Botond Kovács; Enikő Wehmann; Dénes Grózner; Krisztián Bányai; Eszter Zsófia Nagy; Janet Bradbury; Marco Bottinelli; Elisabetta Stefani; Salvatore Catania; Inna Lysnyansky; László Kovács; et al. (PLoS ONE, 2026)
Mycoplasma iowae is an economically significant pathogen that causes reduced hatchability, late embryo mortality and leg deformities, chondrodystrophy and skeletal lesions in poults. While prevention is essential in the control of infection, the appropriate administration of antibiotics may reduce economic losses during outbreaks. As a first step in the exploration of antimicrobial resistance mechanisms in M. iowae , target modification and efflux pump activity were examined in the present study. Point mutations were analyzed in previously described antibiotic binding sites in the whole genome sequences of 99 M. iowae strains. Mismatch amplification mutation assays (MAMAs) were designed and validated for the differentiation of mutations corresponding to elevated minimum inhibitory concentration (MIC) values for fluoroquinolones. Broth microdilution assays were performed to evaluate the effect of efflux pump inhibitors. In the presence of orthovanadate (OV), MIC values were significantly lower than in the absence of OV for spiramycin, tilmicosin, tylosin and oxytetracycline, which may indicate the presence of an active efflux system in M. iowae . Putative promoter regions of efflux-related genes were predicted and characterized. Genetic mutations, previously described in other bacteria, were described to be associated with elevated fluoroquinolone, macrolide and lincomycin MICs in M. iowae , although certain resistant phenotypes remained unexplained, promoting future examinations for deeper insights. The developed MAMAs may support rapid identification of M. iowae strains with elevated MIC values for fluoroquinolones. The better understanding of the efflux pump mechanisms enables the development of alternative methods for the support of therapy against this pathogen.